T lymphocytes and the transfer of immunity to Trypanosoma musculi in mice. - Pouliot, P (1977)
Trypanosoma musculi produces a resolving infection in mice and the immune response is thymus dependent. Spleen cells from immune and from uninfected mice were transferred to T cell-deprived mice and restored their ability to control the infection, the immune cells being effective most rapidly. Treatment of the cells in vitro with anti-theta serum did not impair their ability to restore immunocompetence and it is proposed that, though T-cell dependent, the immune response is effected by theta- cells.